Does investor sentiment impact premiums in M&A transactions? - Hervé, Fabrice; Rouine, Ibtissem; Thraya, Mohamed-Firas; Zouaoui, Mohamed (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This paper examines the impact of investor sentiment on merger outcomes, in particular on bid premiums. Using international data from 54 countries between 2000 and 2021, our results show that investor sentiment has a positive effect on bid premiums. Our findings also suggest that the association between investor sentiment and bid premiums is more pronounced in countries culturally prone to herd-like behavior and overreaction. However, this effect is reduced both in countries with highly efficient institutions and in serial deals. Our results are robust to several checks.